Improving Sensory-Motor Skills in 4-5 Year Old Children through Natural Material Center Learning - Farida Nurul Azmi; Isnaini Budi Hastuti (Universitas Muhammadiyah Surakarta, 2025)
This study aims to describe the implementation of learning at the Natural Materials Center in stimulating the sensory-motor development of children aged 4-5 years. It also seeks to identify effective forms of play activities and examine the supporting and inhibiting factors influencing its implementation. This research employed a descriptive qualitative approach conducted at Kartika III-16 Depo Kindergarten, South Klaten, Central Java. The research subjects consisted of classroom teachers and children aged 4-5 years. Data were collected through observation, interviews, and documentation to obtain comprehensive information regarding learning activities and children's development. Data analysis was carried out through three stages: data reduction, data presentation, and conclusion drawing.The findings indicate that learning at the Natural Materials Center is effective in improving children's sensory-motor skills. Exploratory activities using natural materials such as leaves, sand, clay, water, and grains stimulated hand-eye coordination, strengthened finger muscles, and enhanced precision and concentration. Teachers played a crucial role as facilitators, motivators, and innovators in designing engaging, enjoyable, and developmentally appropriate activities. Supporting factors included teacher creativity in utilizing natural materials, children's enthusiasm for exploration, and active support from parents and the school. However, limited availability of natural materials and differences in children's motor abilities were identified as inhibiting factors.This study demonstrates that learning at the Natural Materials Center not only enhances sensory-motor development but also contributes positively to children's cognitive, socio-emotional, language, and character development in early childhood education.